Differential uptake of nanoparticles by human M1 and M2 polarized macrophages: protein corona as a critical determinant. (November 2016) - Binnemars-Postma, Karin A; ten Hoopen, Hetty WM; Storm, Gert; Prakash, Jai
Aim: To investigate the interaction behavior of M1- and M2-type macrophages with nanoparticles of different sizes with/without the presence of serum.Materials & methods: THP-1 human monocytes were differentiated into M1 and M2 macrophages, and the uptake of silica nanoparticle (50–1000 nm) was studied using flow cytometry and different microscopies.Results: Without serum, higher uptake of all-sized nanoparticles was observed by M1 compared with M2. With serum, uptake of nanoparticles (200–1000 nm) was dramatically increased by M2. Furthermore, serum proteins adsorbed (corona) by nanoparticles were found to be the ligands for receptors expressed by M2, as revealed by SDS-PAGE and gene profiling analyses.Conclusion: The observed differential uptake by M1 and M2 macrophages will help understand the fate of nanoparticles in vivo .